ACHIEVEMENTS OF DEPARTMENT OF PHYSICAL CHEMISTRY OF THE NATIONAL TARAS SHEVCENKO UNIVERSITY OF KYIV AND DEPARTMENT OF WELDING MATERIALS OF PATON WELDING INSTITUTE IN A INVESTIGATING OF SLAG SYSTEMS: UDC 621.791.753.5.048 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
All combination of X-ray research of a constitution of molten welding fluxes and some model slag systems was reviewed. These activities are conducted on physical-chemistry department of the National Taras Shevcenko University of Kiev and in department of welding materials of the Paton welding Institute.
Keywords: -